PENINGKATAN KINERJA SISWA DALAM PEMBELAJARAN IPA-FISIKA PADA MATERI PENGUKURAN DENGAN MODEL DIRECT INSTRUCTION BERBANTUKAN MULTIMEDIA - Fadholi Fadholi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Abstract. The low performance of students in the use of laboratory equipment is often caused by the orientation of teachers who are more focused on achieving the target curriculum and lack of attention to science process skills. The objectives of this study was to describe student activities, students performance, mastery learning outcomes and the response in the 7th grade class of MTsN 1 Candi Laras Utara with a model of Direct Instruction assisted Multimedia for measurement learning. The Class action research conducts in 2 cycles. Each cycle consists of planning, acting, observing, evaluating and reflecting.. The data collected in the form of student activity, students performance , mastery learning outcomes and students' responses, through tests and observation. Results indicated that mastery learning outcomes of students has increased from cycle I to II, which is 75% and 94%. The quality of student performance also increased from 90% to 94%. At the end of second cycle students in implementing the questionnaire responses showed that students rerpon of teaching is good.Keywords: Direct Instruction, Multimedia, Learning Science, Measurement